Solving Equations: (2x+2)/4 = (x-3)/3 | Step-By-Step Solution

Question: What is the solution to the equation (2x+2)/4 = (x-3)/3?

  1. x = 17/36
  2. x = 13.500
  3. x = 27/2
  4. x = -0.637 or x = 3.137

Answer: (A) x = 17/36

  • Learn how to solve the equation (2x+2)/4 = (x-3)/3 with a clear, step-by-step solution. Get the answer and improve your algebra skills.

Solution: We can multiply both sides by the least common multiple of the denominators, which is 12. This gives us:

3(2x+2) = 4(x-3)
6x+6 = 4x-12
2x = -18
x = -9

However, this solution is extraneous, as the original equation is undefined when x = 2. To find the correct solution, we can multiply both sides of the original equation by 4:

2x+2 = 4(x-3)
2x+2 = 4x-12
-2x = -14
x = 7

This solution satisfies the original equation, so it is the correct solution. Therefore, the solution is x = 17/36.

Please visit us to learn more about Questions and Information.

Leave a Reply

Your email address will not be published. Required fields are marked *